Mercury levels in birds and small rodents from Las Orquideas National Natural Park, Colombia (2018)
Mercury (Hg) is a heavy metal known as one of the most toxic elements on the planet. The importance of Hg on living organisms resides on its biomagnification ability. Artisanal gold extraction activities release substantial amounts of this metal, polluting the ecosystems. To assess the impact of gold mining in Las Orquideas National Natural Park (Colombia), total Hg (T-Hg) levels were evaluated from 37 bird and 8 small rodent species collected at two sites within the boundaries of the Natural Park (Abriaqui and Frontino municipalities) that have experienced some gold-extraction history. The mean concentration of T-Hg in bird feathers from both sites was 0.84 ± 0.05 µg/g fw. Differences between species were found according to diet. Total Hg levels were greater on insectivorous (1.00 ± 0.08 µg/g fw), followed by nectarivorous (0.73 ± 0.07 µg/g fw) and frugivorus (0.57 ± 0.09 µg/g fw) species. These Hg levels were greater than those found in feathers from a control sample belonging to the species Penelope perspicax (0.53 ± 0.03 µg/g fw), a frugivorous species living at the Otun Quimbaya Fauna and Flora Sanctuary, a forest without known gold mining. Mercury concentrations in the livers of small rodents were greater in specimens from Frontino (0.15 ± 0.01 µg/g fw) than those from Abriaqui (0.11 ± 0.01 µg/g fw), but levels were not different between species. These results indicate that Hg in birds depends mainly on their diet, but geographical location may affect Hg concentration in rodents. Moreover, Hg sources in natural parks of Colombia may not rely solely on gold mining, atmospheric deposition, among others factors, could be influencing its accumulation in biota. © 2018, Springer-Verlag GmbH Germany, part of Springer Nature.